Dogsled team preparing to leave Dawson for Nome, Alaska, Feb. 11, 1900. - Goetzman, H. J.
Caption on image: "Leaving Dawson for Nome Alaska. A 1200 mile journey. Feb. 11, 1900." PH Coll 246.73 [Meed journal: "Leaving Dawson for Nome, Alaska, Feb 11, 1900. A 1200 mile journey. The overall parka with fur-edged pull-over-hood worn by each driver is made of striped denim such as used for bed ticking. This is used on account of its light weight and it is windproof."] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number